Aplikasi Teori Keperawatan Wiedenbach dan Kolcaba pada Ibu dengan Persalinan Kala Dua Memanjang: Case Study: Indonesia - Rahmawati, Veronica Yeni; Setyowati, Setyowati; Afiyanti, Yati (Sekolah Tinggi Ilmu Kesehatan RS Husada, 2022)
Prolonged second stage of labor is an emergency condition that requires immediate treatment by nurses so that there are no complications for the mother and fetus. The physical and psychological problems experienced by mothers with prolonged second stage of labor include infection, exhaustion, dehydration and even death in the mother. Nursing actions for mothers experiencing prolonged second stage of labor include fluid management, pain management, fetal resuscitation, infection control, anxiety reduction, environmental modification, coping strategies and Early Breastfeeding Initiation. The method used is a case study with a focus on the application of Wiedenbach's need for help theory and Kolcaba's comfort in nursing care for mothers who experience a prolonged second stage of labor. The cases managed in this study were five mothers who experienced a prolonged second stage of labor at two different hospitals in the Greater Jakarta area. Nurses can apply the theory of Wiedenbach's need for help and Kolcaba's comfort in providing nursing care to mothers with prolonged second stage of labor.